Democracia e liberdade de expressão no Brasil: os fundamentos da restrição à expressão na propaganda eleitoral - COSTA, Raissa Campagnaro de Oliveira (2023)
The present research aims to analyze the treatment of freedom of expression in Brazilian electoral law, with emphasis on electoral propaganda, in the light of the liberal-democratic balance model advocated by Robert Dahl, using the legislation and jurisprudence of the Superior Electoral Court and the Regional Electoral Court of Maranhão in the period of 2018 and 2020 related to the positions of State Governor and Mayor. Therefore, this work uses the inductive method of approach, since it intends to make use of norms and judgments of the TSE and TRE-MA, and to analyze them in the light of the basic theory of democracy by Robert Dahl in order to verify the hypothesis raised and propose generalizations. In addition, it is a systematic literature review research, which makes use of bibliographic and documentary research techniques. The study departs from the assumptions of the preference for freedom of expression in Brazil's legal system and the inversion of this primacy in Brazilian electoral propaganda. Subsequently, the research exposes and reflects on Robert Dahl's theoretical framework, which proposes the balance between democracy and individual freedoms, in order to, in the end, investigate the compatibility between the general clause of primacy of freedom of expression in the Brazilian legal system and the rule of restriction of freedom of expression in electoral propaganda, in the normative and jurisprudential dimensions, against the model of liberal-democratic balance proposed by Robert Dahl.